IMPLEMENTASI INTEGRATED MARKETING COMMUNICATION (IMC) PADA PT TOKOPEDIA DALAM MEMPERTAHANKAN PELANGGAN - Adityo Fajar (Jurnal Komunikasi, 2017)
Integrated Marketing Communication (IMC), which is also called integrated marketing communications is the process of development and implementation of various forms of persuasive communication program to customers and prospective customers on an ongoing basis. The importance of the implementation of this IMC in the company has been recognized by PT Tokopedia. Therefore, the purpose of this study is that analyze the implementation of IMC in Tokopedia in retaining customers and constraints faced in the implementation of the IMC. This research method is descriptive qualitative informant number six. The results of this study are implememtasi of IMC on Tokopedia is reflected in the activities of advertising, direct marketing, sponsorship, merchandising, public relations activities and websites aimed at retaining customers. The obstacles encountered in the implementation of the IMC activities is the lack of human resource capacity in terms of communication when providing information to customers and also technical problems in the care of the Website.Keywords: integrated marketing communications, e-commerce, customer retention